IMPLEMENTATION OF THE USE OF SONG AS A METHOD OF LEARNING ENGLISH FOR CHILDREN - Endang Sri Andayani (Institut Pendidikan Tapanuli Selatan, 2022)
Understanding English is essential in life in modern times. This is because English is the most widely spoken language in the world. Especially when in an international environment, English seems to be an obligation.But unfortunately, learning English itself is not so easy, so there needs to be a unique method in the learning process that can increase the effectiveness of the learning outcomes.One suitableway of learning English is to use songs as the method. This study uses a qualitative approach to analyze the use of songs as a method of learning English.The results show many advantages to using songs as a learning method. These advantages include children feelinghappier with the song than learning in class as usual. Then they also learn English subconsciously. These advantages will make it easier for children to learn English than the standard method.